The role of producer in fostering creativity in Child Star - Soemarno, Janice Stefani; Ihwanny, Rista (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
This study offers a fresh perspective on the role of the film producer by examining the creative dimensions of their work, an aspect that remains underexplored in film and animation studies, particularly within the Indonesian context. The research addresses the problem of how film production is often perceived primarily as a managerial or logistical process, rather than as a creative practice. The study aims to investigate to what extent film production can be considered a creative endeavor and how such creativity is expressed in practice. To achieve these objectives, the research examines the role of the producer in fostering creativity during the idea and story development as well as the pre-production stages of the short-animated film Child Star, produced by ONN Studio in Tangerang, Indonesia. This study employs a qualitative phenomenological approach, using direct observation, FGD, and reflective analysis to capture the lived experiences of the producer as a creative agent within the animation production process. The findings reveal that the producer’s role extends beyond financial and organizational responsibilities to include creative decision-making, narrative development, and mediation between artistic vision and production constraints. The study concludes that film production, particularly in independent animation contexts, constitutes a creative practice in which the producer plays a crucial role in shaping the final work. This research contributes to the limited scholarship on Indonesian animation and expands discussions on creative labor in animation production.